2012
DOI: 10.5650/oleoscience.12.25
|View full text |Cite
|
Sign up to set email alerts
|

The State of the Art and Perspective of Structural Study on Skin Stratum Cormeum

Abstract: Based upon the wide q-range X-ray scattering study on stratum corneum, I will introduce that not only the structure of the intercellular lipid matrix but also the structure of soft keratin in the corneocytes plays an impor tant role in function of the stratum corneum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In the test cream, the dry coating film had a repeating structure of approximately 10 nm, this was confirmed by small-and wide-angle X-ray scattering and TEM observation ( Figures 2 and 3 ). It has been reported that the intercellular lipids in the human stratum corneum have a short periodic structure of 6 nm and long periodic structure of 13 nm, 24 and display similarities with the structure of the dry coating formed by the heparinoid cream we developed.…”
Section: Discussionmentioning
confidence: 70%
“…In the test cream, the dry coating film had a repeating structure of approximately 10 nm, this was confirmed by small-and wide-angle X-ray scattering and TEM observation ( Figures 2 and 3 ). It has been reported that the intercellular lipids in the human stratum corneum have a short periodic structure of 6 nm and long periodic structure of 13 nm, 24 and display similarities with the structure of the dry coating formed by the heparinoid cream we developed.…”
Section: Discussionmentioning
confidence: 70%